Natural Rubber Modification Technology and Its Applications - ก้องพารากุล สุวดี (KKU Science Journal, 2013)
Natural rubber or Para rubber is an important natural polymeric resource in Thailand. The outstanding mechanical properties of natural rubber, such as elasticity and tear resistance, are more than synthetic rubber from petrochemical industry. However, natural rubber is easily degraded when exposed to sunlight, heat or non-polar organic solvent. Therefore, natural rubber usages required a modification process to improve its properties and reduce its defects. This review article presents various natural rubber modification methods and its properties of modified natural rubber from previous research articles. This would be an alternative way to improve some properties of natural rubber for further application.